The Mediating Role of Behavioural Intention in the Relationship between Digital Literacy and Technology Acceptance: A Structural Equation Modelling Approach - Zainuddin, Kamilah; Mat Daud, Khairul Azhar; Mahmud, Yus Heary (Online Journal for TVET Practitioners, 2026)
Behavioural Intention (BI) has been widely acknowledged as a critical determinant of technology acceptance. However, the BI as a mediating role between Digital Literacy Skills (DLS) and Digital Technology Acceptance (DTA) remains underexplored, particularly in Technical and Vocational Education and Training (TVET) environments. This study investigates how BI mediates the relationship between students’ DLS, conceptualised using the DigComp framework, and the DTA, framed within the Unified Theory of Acceptance and Use of Technology (UTAUT). A survey of 490 through stratified random sampling with two stage cluster within Malaysian TVET students represented by Politeknik Malaysia students was analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) via SmartPLS 4.0. The research instrument was adapted from established scales and validated through five expert review and pilot testing (n=30, Cronbach’s Alpha > 0.7). The Higher-Order Construct (HOC) model analysis utilised a type 1: reflective-reflective disjoint two-stage approach. The constructs possess excellent internal consistency, as all Composite Reliability (CR) values for Lower Order Construct (LOC) and HOC are well above the 0.70 threshold, exceeding the commonly accepted threshold, indicating strong internal consistency for the higher-order constructs. Results from the mediation analysis confirmed that BI significantly mediates this relationship (?=0.708, t=12.124, p=0.000) in the HOC model analysis rather than in the LOC level. These findings provide empirical evidence of the motivational pathways driving technology acceptance in educational contexts. This study advances theoretical discourse by validating BI as a powerful mechanism linking DLS and DTA, offering practical insights for education practitioners aiming to foster positive attitudes and higher engagement with digital technologies among TVET learners.